2012
DOI: 10.1097/hmr.0b013e31821fa503
|View full text |Cite
|
Sign up to set email alerts
|

Beyond communication

Abstract: The results indicate that SBAR may function as more than a tool to standardize communication among nurses and physicians. Rather, the findings indicate that SBAR may aid in schema development that allows rapid decision making by nurses, provide social capital and legitimacy for less-tenured nurses, and reinforce a move toward standardization in the nursing profession. Our findings further suggest that standardized protocols such as SBAR may be a cost-effective method for hospital managers and administrators to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 35 publications
1
19
0
2
Order By: Relevance
“…[ 33 , 34 ] Communication strategies have been developed in order to provide healthcare practitioners a method for an effective transmission of information in a structured and organized manner. [ 35 , 36 ] In all scenarios of our study, we created events forcing participants to transmit information and orders to other colleagues through the adoption of a structured communication strategy. [ 10 ] We believe that this had a positive effect on knowledge acquisition about team working/communication among students in group S. This finding has been previously reported in studies investigating the benefit of simulation for team working during inter-professional scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…[ 33 , 34 ] Communication strategies have been developed in order to provide healthcare practitioners a method for an effective transmission of information in a structured and organized manner. [ 35 , 36 ] In all scenarios of our study, we created events forcing participants to transmit information and orders to other colleagues through the adoption of a structured communication strategy. [ 10 ] We believe that this had a positive effect on knowledge acquisition about team working/communication among students in group S. This finding has been previously reported in studies investigating the benefit of simulation for team working during inter-professional scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Another antecedent is effective communication. Positive and constructive communication, one definition of effective communication, are the crux of productive interaction and relationship development (Read, 2014;Vardaman et al, 2012). Poor and inappropriate communication can have deleterious consequences that will destroy nurses' workplace social capital (Hofmeyer, 2013).…”
Section: Antecedentsmentioning
confidence: 99%
“…38, 39 Since then, many groups, institutions, and programs have adopted the SBAR model; these include the Agency for Health Care Research and Quality’s Team Strategies and Tools to Enhance Performance and Patient Safety (TeamSTEPPS) program and their Patient Safety Network, the U.S. Department of Defense’s Patient Safety Program, the Institute for Healthcare Improvement, Kaiser Permanente, the National Health Service in the United Kingdom, and Interventions to Reduce Acute Care Transfers (INTERACT) collaborative. 24, 40–45 Experience with using SBAR templates for handoffs suggests that it is a useful communications framework with positive effects on both individuals and organizations.…”
Section: The Discharge Summary As a Handoff Communicationmentioning
confidence: 99%
“…23,4549 Additionally, Vardaman and colleagues observed that use of the SBAR format in handoffs enhanced rapid sharing of clinical contexts, clarified roles and expectations, and increased trust among interdisciplinary team members. 39 The SBAR model also has been shown to facilitate critical thinking and analysis in case discussions in morbidity and mortality conferences. 50,51 …”
Section: The Discharge Summary As a Handoff Communicationmentioning
confidence: 99%